-
A JK flip flop can be implemented by T flip-flops. Identify the correct implementation.
Correct Option: B
Analysis : If you will observe the combinational circuit output expression which is the input for T flip flop is not matching directly, so you should go through the option. If you will solve the combinational circuit of option (B) then
T = (J Qn).(K + Qn)
= J.K + JQn + K.Qn + Qn Qn
= J.K + JQn + K.Qn 0
(∵ Qn. Qn = 0)
= J.K + JQn K.Qn
Now, according to consensus theorem J-K will become redundant term, so it should be eliminated.
Hence, T = JQn + K.Qn which in matching with our desired result and option-(b) is correct answer.